2014
DOI: 10.1136/thoraxjnl-2014-205248
|View full text |Cite
|
Sign up to set email alerts
|

What happens to patients with COPD with long-term oxygen treatment who receive mechanical ventilation for COPD exacerbation? A 1-year retrospective follow-up study

Abstract: We performed a retrospective cohort study of patients with chronic obstructive lung disease (COPD) on long-term oxygen treatment (LTOT) who received invasive mechanical ventilation for COPD exacerbation. Of the 4791 patients, 23% died in the hospital, and 45% died in the subsequent 12 months. 67% of patients were readmitted at least once in the subsequent 12 months, and 26.8% were discharged to a nursing home or skilled nursing facility within 30 days. We conclude that these patients have high mortality rates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…The prognosis for subjects who were discharged with STOT following hospitalization was poor. The overall 1-y survival rate of 61% for the nonpalliative subjects was comparable with previously reported data for subjects hospitalized for heart failure and COPD, which ranged from 56% to 67% [34][35][36][37] and from 55% to 78%, [38][39][40][41][42] respectively. A cohort study of a sample of Medicare beneficiaries Ͼ 65 y old from the United States reported 3-y mortality rate of 39.5% for those who were admitted to the ICU during hospitalization.…”
Section: Discussionsupporting
confidence: 87%
“…The prognosis for subjects who were discharged with STOT following hospitalization was poor. The overall 1-y survival rate of 61% for the nonpalliative subjects was comparable with previously reported data for subjects hospitalized for heart failure and COPD, which ranged from 56% to 67% [34][35][36][37] and from 55% to 78%, [38][39][40][41][42] respectively. A cohort study of a sample of Medicare beneficiaries Ͼ 65 y old from the United States reported 3-y mortality rate of 39.5% for those who were admitted to the ICU during hospitalization.…”
Section: Discussionsupporting
confidence: 87%
“…These included one direct question about whether participants trusted the decision aid, one concerning confidence in the accuracy of the estimates given, and one asking whether participants thought the numbers could be wrong. Most patient participants (N=11; 84.6%), and all surrogate participants trusted the contents of the decision aid, stating that: they trusted the source of the information (both the fact that the decision aid was linked to our health system, and because the decision aid itself contains a resources section where we provide information on how the estimates were generated, including the sources from which the estimates were generated) 13 ; the information was consistent with what they had experienced; and the decision aid was not linked to any advertisements or corporate sponsors. However, on average, patient and surrogate participants stated that they were only about 60% sure (median: 50% and 70% for patient and surrogates) that the estimates given were correct, and almost all patient and surrogate participants stated that these numbers could be incorrect because: peoples’ outcomes vary; the research could be based on people with unspecified co-morbidities; or the information was inconsistent with prior experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found the in-hospital mortality rate to be between 20–30% for patients requiring mechanical ventilation for COPD exacerbation [2730]. In addition, patients with COPD have been found to have high neutrophil, macrophages, and CD8 + T cells in the lungs.…”
Section: Discussionmentioning
confidence: 99%